Pain-related vertex evoked potentials: comparison of surface electrical to heat stimulation - Guiloff, Roberto J.; Campero, Mario; Barraza, Gonzalo R.; Treede, Rolf-Detlef; Matamala, Jose M.; Castillo, Jose L. (Journal of clinical neurophysiology, 2023)
Introduction: - Demonstration of nociceptive fiber abnormality is important for diagnosing neuropathic pain and small fiber neuropathies. This is usually assessed by brief heat pulses using lasers, contact heat, or special electrodes. We hypothesized that pain-related evoked potentials to conventional surface electrical stimulation (PREPse) can index Aδ afferences despite tactile Aß fibers coactivation. PREPse may be more readily used clinically than contact heat evoked potentials (CHEPS). - Methods: - Twenty-eight healthy subjects. Vertex (Cz-A1/A2) recordings. Electrical stimulation of middle finger and second toe with conventional ring, and forearm/leg skin with cup, electrodes. Contact heat stimulation to forearm and leg. Compression ischemic nerve blockade. - Results: - PREPse peripheral velocities were within the midrange of Aδ fibers. N1-P1 amplitude increased with pain numerical rating scale graded (0-10) electrical stimulation (n = 25) and decreased with increasing stimulation frequency. Amplitudes were unchanged by different presentation orders of four stimulation intensities. PREPse N1 (∼130 milliseconds) and N2 (∼345 milliseconds) peaks were approximately 40 milliseconds earlier than that with CHEPS. PREPse and CHEPS N1-N2 interpeak latency (∼207 milliseconds) were similar. PREPse became unrecordable with nerve blockade of Aδ fibers. - Conclusions: - PREPse earlier N1 and N2 peaks, and similar interpeak N1-N2 latencies and central conduction velocities, or synaptic delays, to CHEPS are consistent with direct stimulation of Aδ fibers. The relation of vertex PREPse amplitude and pain, or the differential effects of frequency stimulation, is similar to pain-related evoked potential to laser, special electrodes, or contact heat stimulation. The relationship to Aδ was validated by conduction velocity and nerve block. Clinical utility of PREPse compared with CHEPS needs validation in somatosensory pathways lesions.
Gesehen am 22.07.2024